Sanziguben polysaccharides improve diabetic nephropathy in mice by regulating gut microbiota to inhibit the TLR4/NF-κB/NLRP3 signalling pathway - Fan Wang; Chang Liu; LingZhi Ren; YanYang Li; HongMei Yang; Yang Yu; WeiPing Xu (Taylor & Francis Group, 2023)
AbstractContext Sanziguben (SZGB) is an empirical prescription used in traditional Chinese medicine to treat diabetic nephropathy (DN). As an abundant and primarily effective component of SZGB, Sanziguben polysaccharides (SZP) can be digested by flora to generate biological activity.Objective Our study aimed to clarify the potential mechanism of SZP in improving chronic DN.Materials and methods Male db/db mice were randomized into DN, SZP (500 mg/kg) and metformin (MET, 300 mg/kg) groups. Wild-type littermates served as the normal control (NC) group. The drug was orally administered for 8 weeks. Enzyme-linked immunosorbent assay was used to detect the inflammatory factors. Proteins related to inflammation were evaluated using western blotting and immunohistochemical examination. Gut microbiota was analysed using 16S rRNA sequencing.Results SZP significantly reduced 24 h urine albumin (p < 0.05) of DN mice. Compared to DN group, SZP significantly decreased the homeostasis model assessment of insulin resistance index, serum creatinine and blood urea nitrogen levels (20.27 ± 3.50 vs. 33.64 ± 4.85, 19.22 ± 3.77 vs. 32.52 ± 3.05 μmol/L, 13.23 ± 1.42 vs. 16.27 ± 0.77 mmol/L, respectively), and mitigated renal damage. SZP also regulated gut microbiota and decreased the abundance of Gram-negative bacteria (Proteobacteria, Klebsiella and Escherichia-Shigella). Subsequently, SZP reduced lipopolysaccharides levels (1.06- to 1.93-fold) of DN mice. Furthermore, SZP inhibited the expression levels of TLR4, phospho-NF-κB p65, NLRP3 proteins and interleukin (IL)-18 and IL-1β.Conclusions These results demonstrated that SZP improved intestinal flora disorder and inhibited the TLR4/NF-κB/NLRP3 pathway to alleviate DN.